Flexible and stretchable polyaniline supercapacitor with a high rate capability. Issue 4 (6th March 2020) - Huang, Zhixuan; Ji, Zhenyuan; Feng, Yuping; Wang, Panpan; Huang, Yan
Abstract: Flexible electronics are currently highly favored because of their promising applications in flexible displays, artificial electronic skin, wearable devices etc . Exploiting flexible energy storage systems, which are supercapacitors, that have a decent electrochemical performance as well as flexibility and stretchability is essential to promote the development of flexible electronic products. In this work, a flexible and stretchable polyaniline (PANI) supercapacitor based on a conductive stainless steel mesh was developed via a simple electrodeposition route with an elastic gel polyvinyl alcohol polymer (PVA)/phosphoric acid (H3 PO4 ) electrolyte, which exhibits a considerable rate capability and mechanical properties. The as‐prepared capacitor delivers a specific capacitance of 282 F g −1 under a specific current of 2.5 A g −1 . Meanwhile, the PANI capacitor exhibits perfect pseudocapacitance behavior at low scan rates (up to 50 mV s −1 ) and great capacitive characteristics at high scan rates up to 5000 mV s −1 . More impressively, this supercapacitor displays excellent tolerance against mechanical deformation, including bending, folding and stretching, even to 20%, with a well‐maintained capacitance. This stretchable PANI supercapacitor with a high rate capability provides a facile and cost‐effective route for the design of flexible energy storage devices. © 2020 Society of Chemical Industry Abstract : A flexible and stretchable supercapacitor was fabricated via electrodeposition of polyaniline with a high capacitance of 290 F g −1 when being stretched to 20%.